Obdavčitev delitvene in digitalne ekonomije - Šumrada, Nana (Podjetje in delo, 2018)
This article presents the current legislative work of the EU in the field of digital economy taxation and solutions adopted by a number of EU Member States as to the sharing economy taxation. Currently, there are plans for a common EU solution for digital economy taxation and a variety of solutions regarding sharing economy taxation at the level of Member States.
Keywords: davek od dohodkov pravnih oseb v EU; obdavčitev delitvene ekonomije; obdavčitev digitalne ekonomije